Evaluación de elementos premoldeados de hormigón utilizados en instalaciones de crianza de ganado porcino en ambiente agresivo. Recomendaciones de fabricación - Oshiro, Ángel; Positieri, M.; Baronetto, C.; Raggiotti, B. (Revista ALCONPAT, 2013)
The modern installations for the intensive rearing of pigs are constructed based on precast concrete elements that are assembled on site in large areas covered and which are subject to an aggressive environment and in the feces they produce vapors, causing a premature replacement of parts by the low durability of the same. The paper presents the results of a study on precast concrete (unworn) that make up the structure in order to verify its performance in service conditions and make recommendations to assure its correct performance. Witnesses were extracted from the parts and measured the resistance to compression, speed of passage of the ultrasonic wave, capillary absorption, absorption and permeability to air. The results obtained allow us to qualify to the concrete between regular and good and presents the recommendations should be considered when manufacturing the precast elements to ensure their durability.